Identification of the novel HLA‐A*01:200 allele by sequence‐based typing in a Croatian individual. (4th April 2016) - Maskalan, M.; Grubic, Z.; Jankovic, K. Stingl; Cepulic, B. Golubic; Zunec, R.
Abstract : The new allele HLA‐A*01:200 differs from A*01:12 by four nucleotide substitutions in exon 3.